Pelatihan Bahasa Inggris Aparatur Desa Purworejo Pesawaran Menuju Pelayanan Publik Berkualitas - Lidya , Lidya Ayuni Putri; Hendrawaty, Ernie; Faisol, Ahmad; Suningsih, Sri; Sakinah, Tazkiyah; Sumanda Syafis, Kamadie (Jurnal Nusantara Mengabdi, 2024)
Purpose: The primary objective of this service was to enhance the English language communication skills of the officials in Purworejo Village, District Negeri Katon, Pesawaran Regency. This improvement aims to support the creation of higher-quality, efficient, and responsive public services in the context of globalization. Methodology/approach: The training utilized interactive methods, including lectures, discussions, and practical exercises. Tools used included pre-tests and post-tests to evaluate participants' knowledge and skills. The approach involved a systematic process: preparation (coordination and logistics), execution (delivery of training content by experts), and feedback (assessment through testing). Results/findings: The training program significantly improved 30 participants' English language proficiency, as evidenced by a marked increase in post-test scores compared to pre-test results. Participants' average scores improved by 20 points, demonstrating a substantial enhancement in their speaking skills. This improvement also translated into greater confidence in using English in professional contexts. Limitations: The training program was limited by its short duration, which may not have allowed for deep mastery of English. Additionally, the group setting may not have addressed individual learning needs, and the assessments focused on immediate progress rather than long-term retention and practical application of skills. Contribution: The service successfully achieved its goal of enhancing English communication skills among the village officials. The interactive and practical approach to training proved effective in improving language proficiency and confidence. This initiative not only better equips the officials to meet the demands of globalization but also enhances the overall quality of public service in their community.